Historical Development of Alleviating Urban Poverty - Şahinoğlu, İlker (Fırat University, 2023)
The concept of poverty and anti-poverty practices have always occupied an important place in social life and on the agenda of governments. Practical examples highlight the transformation of these facts and the perception of poverty in the historical process. Today, the concept is mainly addressed at the urban scale, particularly in developing and developed countries. Especially in the last quarter of the 20th century, there has been a major process of transformation in poverty and welfare regimes in response to economic, political and social changes. In this period in which the understanding of the welfare state has weakened, the rapid change in literature is largely attributed to the dominance of neoliberalism. Because during this period, neoliberalism concentrated on establishing a new economic order to secure the power of the ruling classes. For the establishment of this new order, various practices such as downsizing of the public sector, privatizations, flexibility of employment markets, and reduction of labor costs began to spread on a global scale. In parallel with these structural changes in the economy, we can see that there have been significant changes in poverty and anti-poverty practices. In this context, in this study, the transformation of urban poverty is discussed and the change in the approach of fighting against urban poverty in line with the development of social policy.

Yoksulluk kavramı ve yoksullukla mücadele uygulamaları toplumsal yaşamda ve devletlerin gündemlerinde her dönem önemli yer tutmuşlardır. Uygulama örnekleri tarihsel süreçte bu olguların ve yoksulluk algısının dönüşümünü ortaya koymaktadırlar. Günümüzde kavram özellikle gelişmekte olan ve gelişmiş ülkelerde büyük ölçüde kentsel ölçekte ele alınmaktadır. 20. yüzyılın özellikle son çeyreğinde hem yoksulluk hem de refah rejimlerinde ekonomik, siyasi ve toplumsal değişimlere bağlı olarak büyük bir dönüşüm süreci yaşanmıştır. Refah devleti anlayışının zayıfladığı bu dönemde, karşılaşılan hızlı dönüşüm literatürde büyük ölçüde neoliberalizmin hâkim hale gelmesine dayandırılmaktadır. Çünkü bu dönemde neoliberalizm hâkim sınıfların iktidarını sağlamak üzere yeni bir ekonomik düzen tesis etmeye odaklanmıştır. Bu yeni düzenin tesisi için ise öncelikli olarak kamu kesiminin küçültülmesi, özelleştirmeler, istihdam piyasalarının esnekleştirilmesi, işgücü maliyetinin düşürülmesi gibi çeşitli uygulamaları küresel ölçekte yaymaya başlamıştır. Ekonomideki bu yapısal dönüşümlerle birlikte yoksulluğun ve yoksullukla mücadele uygulamalarının da önemli değişim yaşadıkları görülmektedir. Bu bağlamda çalışmada kentsel yoksulluğun dönüşümü ele alınmakta ve sosyal politikanın gelişimi doğrultusunda kent yoksulluğuyla mücadele yaklaşımında görülen değişime değinilmektedir.
KENT YOKSULLUĞUNA MÜDAHALENİN TARİHSEL GELİŞİMİ